(untitled) (Journal of Interdisciplinary Insights, 2024)
Industry collaboration is increasingly recognized as an impactful approach for enhancing innovation and entrepreneurship education. However, significant barriers continue to impede effective integration of industry linkages into China’s educational institutions. This study aims to identify and critically analyze major obstacles to collaborative initiatives between academia and industry within the context of entrepreneurship education in China. Adopting a mixed-methods approach, the research utilizes interviews, case studies, and surveys to explore the perspectives of educators, students, and industry professionals. Key barriers identified encompass structural rigidities, communication gaps, motivational mismatches, and cultural divergences between educational settings and industry landscapes. The findings highlight critical strategies for overcoming obstacles to collaboration, including boundary-spanning leadership, incentivization structures, cultural alignment initiatives, and communication platforms. By delineating barriers and change strategies, this study contributes practical insights to strengthen synergistic relationships between industry and academia for enriching innovation and entrepreneurship education in China.